Interrelationships between Public Open Space, Common Pool Resources, Publicness Levels and Commons Dilemmas: A Different Perspective in Urban Planning (International Journal of Built Environment and Sustainability, 2019)
Public open space (POS) is central to the environment, and oftentimes spatial and architectural designs are emphasised in urban planning as part of creating quality POS. However, such initial design and planning of POS may not adequately encapsulate the sustainability dimensions of the complex social-ecological behavioural patterns of POS consumption and management, hence resulting in space mismanagement, underinvestment, and quality degradation. This phenomenon is particularly true and relevant in the context of government/state-owned POS. Therefore, an objective of this perspective paper, coupled with the concepts of the publicness levels, is to provide a different understanding of exclusivity and subtractibility natures of POS, primarily using the theory of common pool resources (CPRs), which subsequently helps explain and rationalise the perennial, adversarial POS management, quality and sustainability status quo. This paper reveals that, instead of being considered as pure public goods, scarce POS owns two inherent attributes of CPR, namely non-excludable and subtractive (rivalrous) that are ultimately susceptible to social/commons dilemmas, covering the Tragedy of the commons (overexploitation), management shirking, free-riding, underuse, disuse, and moral hazard, which lead to degraded, unsustainable POS. The commons or CPR theory can indeed offer a new paradigm shift, making urban planners and landscape managers to embrace that the unexclusive natures of CPR-based POS are truly finite and depletable and thus vulnerable to POS dilemmas. Hence, to achieve quality, sustainable POS commons, effective governance in terms of consumption and consistent management is vital. For future research, urban design as a necessary societal role is suggested, which has established the need for effective allocation of POS management via an adaptive institutional property rights design.
Keywords: Public Open Space (POS); Common Pool Resource (CPR); Commons/Social Dilemmas; Urban and Neighbourhood Commons; New Institutional Economics